1996
DOI: 10.3354/dao026181
|View full text |Cite
|
Sign up to set email alerts
|

Mode of infection and spread of Vibrio anguillarum in turbot Scophthalmus maximus larvae after oral challenge through live feed

Abstract: The infection route of the inanne fish pathogen Vibrio anguillarum was studied after oral challenge of juvenile turbot Scophthalmus maximus L. through a live feed. Artemia nauplii were incubated In a suspension of V anguillarum cells, and subsequently fed twice to the fish. All challenged fish died within 4 d after the first challenge, whde no mortality occurred in the non-challenged controls The results of an immunohistochemical examination of the sectioned f~s h samples clearly demonstrated that V anguillaru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(91 citation statements)
references
References 12 publications
2
85
0
4
Order By: Relevance
“…Our results suggest that a route of entry other than bath-challenge alone is required or, alternatively, that a combination of both bath and oral exposure is needed. Experiments that deliver challenges via live feed have been performed on turbot Scophthalmus maximus larvae (Grisez et al 1996, Planas et al 2005 but to the best of our knowledge no such experiments have been performed on cod larvae. Another explanation for the lack of pathogenicity is the possibility of quorum sensing.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that a route of entry other than bath-challenge alone is required or, alternatively, that a combination of both bath and oral exposure is needed. Experiments that deliver challenges via live feed have been performed on turbot Scophthalmus maximus larvae (Grisez et al 1996, Planas et al 2005 but to the best of our knowledge no such experiments have been performed on cod larvae. Another explanation for the lack of pathogenicity is the possibility of quorum sensing.…”
Section: Discussionmentioning
confidence: 99%
“…Grisez et al (145) showed that infection of turbot (Scophthalmus maximus) larvae by V. anguillarum occurs in the intestinal epithelium, where the pathogen invades the bloodstream and spreads to different organs, culminating in death of the fish. More recently, Ringo et al (326) detected bacterial endocytosis in the pyloric ceca and midgut of arctic charr (Salvelinus alpinus L.) adults and suggested that the whole gastrointestinal tract of fish may be subject to infection.…”
Section: Role In Aquaculturementioning
confidence: 99%
“…Several culturedependent and -independent studies have confirmed the ubiquity of vibrios, and suggested Vibrio populations generally comprise approximately 1% (by molecular techniques) of the total bacterioplankton in estuaries (19), in contrast to culture-based studies demonstrating that vibrios can comprise up to 10% of culturable marine bacteria (20). Clearly, vibrios are ubiquitous and abundant in the aquatic environment on a global scale, including both seawater and sediment (19,(21)(22)(23)(24)(25), and repeatedly shown to be present in high densities in and on marine organisms, such as corals (26), fish (27)(28)(29), mollusks (30), seagrass, sponges, shrimp (28,31), and zooplankton (16,17,28,32,33).…”
mentioning
confidence: 99%